2018
DOI: 10.1088/1361-665x/aac3fb
|View full text |Cite
|
Sign up to set email alerts
|

Design of a bistable electromagnetic coupling mechanism for underactuated manipulators

Abstract: Electromagnetic clutches have been widely used in underactuated lightweight manipulator designs as a coupling mechanism due to their advantages of fast activation and electrical controllability. However, an electromagnetic clutch consumes electrical energy continuously during its operation. Furthermore, conventional electromagnetic clutches are not fail-safe in unexpected power failure conditions. These factors have a significant impact on the energy efficiency and the safety of the design, and these are vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Other technologies, such as bistable compliant mechanisms, were also proposed for specific application, such as the monolithic design in [18]. Overall, research trends have shown that DEAs and electromagnetic actuators are favoured in tasks that require accurate positioning but struggle with high payloads [19][20][21][22][23][24]. Conversely, pneumatics and SMAs are able to withstand higher forces, but at the cost of lower accuracy and efficiency, and increased size.…”
Section: A Binary Mechatronic Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other technologies, such as bistable compliant mechanisms, were also proposed for specific application, such as the monolithic design in [18]. Overall, research trends have shown that DEAs and electromagnetic actuators are favoured in tasks that require accurate positioning but struggle with high payloads [19][20][21][22][23][24]. Conversely, pneumatics and SMAs are able to withstand higher forces, but at the cost of lower accuracy and efficiency, and increased size.…”
Section: A Binary Mechatronic Systemsmentioning
confidence: 99%
“…Given the similar performance of the Three-Groove and Kelvin Clamp couplings, the first [32] has been selected for the mechanisms in Section III because of its symmetrical layout. Any Manipulation [8] Any Manipulation [9][10][11] DEA a Biomedical [12] Electromagnets Biomedical [13] SMA b Space [14][15] SMA b Grasping [16] SMA Manipulation [17] Pneumatics Manipulation [18] Compliance Space [19] Electromagnets Tooling [20][21] Electromagnets Flytrap [22][23] Electromagnets Manipulation [24] Electromagnets Origami robots a DEA: Dielectric Elastomer Actuation b SMA: Shape Memory Alloy However, the constructive solutions shown in this paper are only two examples of implementation of the proposed concept, which can be realized with a wide variety of geometries.…”
Section: B Kinematic Couplingmentioning
confidence: 99%
See 1 more Smart Citation